2016
DOI: 10.5430/wje.v6n4p22
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Version of the Inventory of Suicide Orientation - ISO 30 in Adolescent Students of Educational Institutions in Medellin - Colombia

Abstract: Inventory of Suicide Orientation -ISO 30, it is a self-report scale that measures risk of adolescents suicide orientation. Although the risk of adolescents suicide is on the public agenda in Colombia actually, there is no study to analyze the psychometric properties of ISO 30, and for this reason, the present study is conducted with a random sample of 604 adolescent students (48% were male and 52% female with an average age of 14 and a deviation of 1.9 years). Methods: A confirmatory factor analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These results are relevant because suicidal orientation assessed with the ISO‐30 is an indicator of suicide risk (King, & Kowalchuk, ) and has been demonstrated to be related to hopelessness ( r = .64, p < .01), suicide ideation (correlations ranging from .43 to .78, p < .01 in all cases; King, & Kowalchuk, ), and suicidal behaviors including past suicide attempt, threat of suicide attempt, and self‐reported suicide likelihood ( r = .54, p < .001; Osman et al, ). Further, suicidal orientation is inversely related to reasons for living (correlations ranging from −.57 to −.66, p < .001 in all cases; Osman et al, ; Paniagua‐Suárez et al, ). Because the purpose of this instrument is not to predict suicidal behavior (King, & Kowalchuk, ), and the predictive validity for suicidal ideation and suicide attempt has been found only in clinical samples (King, & Kowalchuk, ; Osman et al, ), the results of the current study should be interpreted just as a reduction in the indicators of suicide risk.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results are relevant because suicidal orientation assessed with the ISO‐30 is an indicator of suicide risk (King, & Kowalchuk, ) and has been demonstrated to be related to hopelessness ( r = .64, p < .01), suicide ideation (correlations ranging from .43 to .78, p < .01 in all cases; King, & Kowalchuk, ), and suicidal behaviors including past suicide attempt, threat of suicide attempt, and self‐reported suicide likelihood ( r = .54, p < .001; Osman et al, ). Further, suicidal orientation is inversely related to reasons for living (correlations ranging from −.57 to −.66, p < .001 in all cases; Osman et al, ; Paniagua‐Suárez et al, ). Because the purpose of this instrument is not to predict suicidal behavior (King, & Kowalchuk, ), and the predictive validity for suicidal ideation and suicide attempt has been found only in clinical samples (King, & Kowalchuk, ; Osman et al, ), the results of the current study should be interpreted just as a reduction in the indicators of suicide risk.…”
Section: Discussionmentioning
confidence: 94%
“…To evaluate suicidal orientation, we used the ISO‐30 (King & Kowalchuk, , Brazilian version of Silva et al, in press), which is a self‐reported instrument with 30 items, with an internal consistency of 0.84. It was developed using two samples of adolescents in both clinical and school settings (King, & Kowalchuk, ), and it has been validated in clinical (King, & Kowalchuk, ; Osman et al, ; Piersma, & Boes, ) and community student samples (Casullo, ; King, & Kowalchuk, ; Liporace, & Casullo, ; Paniagua‐Suárez, González‐Posada, & Rueda‐Ramírez, ). ISO‐30 has adequate convergent, discriminant, and predictive validity (King, & Kowalchuk, ; Osman et al, ; Paniagua‐Suárez et al, ).…”
Section: Methodsmentioning
confidence: 99%